EFEKTIVITAS PSIKOTERAPI PROFETIK TERHADAP KESEJAHTERAAN PSIKOLOGIS PADA WARGA BINAAN PEMASYARAKATAN - Wanodya Kusumastuti (Psyche: Jurnal Psikologi, 2020)
Uncontrollable aggressive behavior can trigger forms of crime that lead to criminal acts. This study aims to look at the effect of prophetic psychotherapy on the psychological well-being of prisoners. Research respondens was 13 peoples who had served a minimum detention period of 2 years. The research method uses action research, namely by conducting a diagnosis related to psychological problems experienced by prisoners and making action plan, taking action and resulting these interventions are used as basic research reflections. The results showed that prophetic psychotherapy had a significant influence to improve psychological well-being with p value 0.001 < 0.05 with t= 4.441, which menass that prophetic psychotherapy give significant effect of the psychological well-being. Fostered people feel the change that is a good emotional regulation, getting closer to God, being grateful, increasing quality of worship and having optimism in living life. Keywords: psychological well being, prophetic psychotherapy, prisoners